Analisis Pengaruh e-WOM, Brand Attitude, dan trust terhadap Purchase Intention Eco-Friendly Transport di Surakarta - Firyal Nuzulul Fitri; Muzakar Isa (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to test the analysis of the influence of E-Wom, brand attitude, and trust on purchase intention for eco-friendly transport in Surakarta. The population used in this research are users of eco-friendly transport products in Surakarta. The sample used was users of eco-friendly transport products aged 17 and over, and 309 respondents were domiciled in the Surakarta area. Data analysis with partial least squares (PLS) This study's quantitative data was analysed using 3.0 analysis. The results of the study suggest that electronic word-of-mouth (e-wom) significantly and favourably influences the confidence and perception of the brand among environmentally conscious transportation consumers. Additionally, trust exerts a substantial and favourable influence on the purchase intention of said consumers. Furthermore, the purchase intention is significantly and favourably impacted by brand attitude. Additionally, e-women significantly and positively affect the purchase intent of environmentally conscious transportation consumers,.